Sanksi Adat dalam Perceraian Suku Dayak Ngaju Kalimantan Tengah - Christine, Winne; Santhy, Wika Yudha; Ariyanti, Ariyanti; Anggriawan, Ferry (University of Merdeka Malang, 2023)
In this thesis the author carries the theme “Implementation of Customary Sanctions in Divorce of the Dayak Ngaju Tribe Central Kalimantan (Study in Parenggean District, Central Kalimantan)”, The application of customary sanctions in the form of singers (customary fines) is a hereditary tradition owned by the Dayak Ngaju people in the event of a divorce, which is cultivated and preserved in the Dayak Ngaju traditional marriage process. In this case the marriage agreement is held to regulate and determine matters that are considered as a future problem in married life. In practice, the party who made a mistake will pay the customary fine in the presence of the Damang Head of Customs. Obstacles in the application of customary sanctions in the divorce of the Dayak Ngaju Tribe are when the party who is guilty of having to pay the penalty does not have enough money to pay it so the other party has to wait and make several reprimands to that party, the problem of imposing customary sanctions is also constrained when each each party does not have an agreement to determine who should pay the fine because both parties feel innocent even though it has been decided by the authorities (Damang Kepala Adat). Furthermore, what becomes an obstacle in the application of customary sanctions is when the divorcing party does not want to be responsible for paying the singer (customary fine) that has been stated in the customary marriage agreement.